Bibliometric analysis and review of Building Information Modelling literature published between 2005 and 2015 - Santos, Rúben; Costa, António A.; Grilo, António (Automation in construction, 2017)
The use of Building Information Modelling (BIM) has increased in recent years, mostly due to the potential of the methodology for improving construction project performance and efficiency. With a view to achieving a better understanding of the research work on this subject, this paper conducts a bibliometric analysis and a review of existing literature on BIM focusing on the last decade. The authors selected the articles published in journals with an impact factor higher then 1.0, as well as the top 100 most cited articles. The search resulted on 381 articles, which were then categorised in order to systematise the research conducted over the years. The authors have not only analysed the existing literature but also highlighted new emerging fields in BIM research, being possible to identify Collaborative Environments and Interoperability, Sustainable Construction, BIM Adoption & Standardisation, and BIM Programming as the categories with the most significant growth in the last years. It was also observed that the most researched topics were related with the development of BIM tools, the study of BIM adoption worldwide, the energy simulation using BIM-based information and, more recently, with the semantic interoperability and ontology. On the other hand, the study on BIM at the academic level is very small, as well as parametric modelling and quantity take-off. •A bibliometric analysis of BIM literature until 2015 resulted in 381 papers.•BIM research is exponentially increasing in the last five years.•Study on BIM adoption, laser scanning and literature reviews are the most cited articles.•BIM Tool Development, Semantic BIM & Ontology, and Laser Scanning are new trends.•BIM training & education, BIM-GIS, and Quantity Take-off are gaps in the literature.